Association between NT-proBNP Level and the Severity of COVID-19 Pneumonia - Lan Wang; Fei Chen; Lin Bai; Lang Bai; Zhixin Huang; Yong Peng (Cardiology Research and Practice)
In this study, we investigated the association between the plasma NT-proBNP level at admission and the severity of COVID-19 pneumonia. For this retrospective, single-centre cohort study, we enrolled consecutive patients from February 9 to March 4, 2020, in a COVID-19 ward of Hubei General Hospital (East Branch) in Wuhan, which is a government-assigned centre for COVID-19 treatment. Diagnosis was confirmed by microbiological and radiographic findings following the interim guidance of the World Health Organization (WHO). A total of 91 (92.9%) patients were finally included in this study. The median age of the patients was 61 years (IQR, 47–69), and 39 (43.0%) of them were male. Two cases of death were reported (2.3%). Twenty-three patients (25.3%) had NT-proBNP levels above 300 pg/ml. Higher NT-proBNP levels were associated with worse PSI and CT scores. The natural logarithm of the NT-proBNP level was positively correlated with the PSI and CT scores (PSI score: rS = 0.396, P=0.001; CT score: rS = 0.440, P<0.001). Patients with NT-proBNP ≥300 pg/ml showed a potential risk for higher mortality than patients with NT-proBNP <300 pg/ml (mortality rate, 8.7% vs. 0%; P=0.062). The plasma NT-proBNP level of COVID-19 patients was significantly related to the severity of pneumonia.